(untitled) (Indian Journal of Nematology, 2024)
Bioformulations significantly reduced population of Meloidogyne incognita, root galling severity and enhanced fruit yield of okra under field conditions. The population of M. incognita was relatively low in the plots receiving seed treatment with Paecilomyces lilacinus, Pochonia chlamydosporia and Pseudomonas fluorescens (10g/kg seed). However, the highest fruit yield was obtained with the application of P. lilacinus (10g/kg + FYM 10t/ha). Results of second season in the same fields during October-January, 2011-2012 confirmed that at higher initial nematode population (465/200cm3soil), adoption of above treatments showed little impact on reduction of nematode population, infection on okra and root galling severity. However, seed treatment with bioformulations (at 10g/kg of seed) proved as the most economical recommendation for root-knot nematode management in okra. This was followed by application of P. lilacinus (10g/kg seed) +FYM at 10t/ha. The study results demonstrated using bioformulations as seed treatment in the highly infested fields of root knot nematode is ineffective for the protection of okra from the infestation of root-knot nematode.